Resistência de genótipos de sorgo a Contarinia sorghicola (Coq.) (Diptera: Cecidomyiidae) e Diatraea saccharalis (Fabr.) (Lepidoptera: Pyralidae) e influência sobre parasitóides - Lara, Fernando Mesquita [UNESP]; Foss, Mauro R. D. A. [UNESP]; Boiça Jr., Arlindo L. [UNESP]; Trigo, José G. [UNESP] (Sociedade Entomológica do Brasil, 1997)
Avaliou-se a resistência de genótipos de sorgo (Sorghum bicolor) a Contarinia sorghicola (Coq.) e Diatraea saccharalis (Fabr.) e sua influência sobre parasitóides. Foram realizados ensaios em duas épocas de plantio, anotando-se o número de insetos (pragas e parasitóides) e calculando-se a percentagem de parasitismo. O genótipo AF-28 destacou-se como o mais resistente às duas espécies pragas, ocorrendo o inverso com o TX-2567; as maiores percentagens de parasitismo de C. sorghicola por Tetrastichus sp. (Hymenoptera: Eulophidae) ocorreram em BR-501 (36,7%) e AF-28 (20,0%); as maiores percentagens de parasitismo de D. saccharalis por Cotesia flavipes (Cam.) (Hymenoptera: Braconidae) foram observadas em BR-601 e 3DX-57 (50 e 40%).

The resistance of some sorghum genotypes (Sorghum bicolor) to Contarinia sorghicola (Coq.) and Diatraea saccharalis (Fabr.) was evaluated in the field, as well the influence of genotypes over the parasitism by Tetrastichus sp. (Hymenoptera: Eulophidae) and Cotesia flavipes (Cam.) (Hymenoptera: Braconidae). Two experiments were conducted, in different planting dates. AF-28 genotype was the most resistant to both pests, while TX-2567 was the most susceptible. Sorghum midge parasitism was higher (36.7%) on BR-501 and AF-28 (20.0%) than on the other genotypes. Parasitism of the sugarcane borer by C. flavipes was higher on BR-601 and 3DX-57 (50 and 40%)and was not observed on SC-3541 and TX-2567 genotypes.
Resistance of sorghum genotypes to the sorghum midge Contarinia sorghicola (Coq.) and sugarcane borer Diatraea saccharalis (Fabr.) and influence on parasitoids
Keywords: Insecta; Cotesia flavipes; Tetrastichus sp; Host plant resistance; Insecta; Cotesia flavipes; Tetrastichus sp; Resistência de plantas